THE FEATURES OF BASIC MODELING TOOLS OF 3D OBJECTS IN SKETCHUP - MIKHALEVSKYI, VITALII (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Recently, the intuitive-oriented program for designers and architects, which is used to quickly create three-dimensional models of objects, structures, buildings and interiors - SketchUp, has gained widespread recognition in the world of 3D. So now almost all other developers include in their software products or direct support for models (files) SketchUp, or data exchange with it through special plug-ins. SketchUp is designed primarily for sketch, searchable 3D modeling in three-dimensional space. However, SketchUp is successfully used to develop a variety of projects in all genres of design, advertising, engineering design, film and game production. The saltation in the increasing popularity of SketchUp has occurred since the program was "tied" to the new owner’s Internet projects - Google 3D models and Google Earth. The reason for choosing and acquiring SketchUp by Google, apparently, was its simplicity and accessibility. By creating a model of an architectural structure or any other object in SketchUp, users could place their creations in the public online collections of Google. So, in particular, the selection of collections "Cities under development" contains several thousand models of real architectural buildings of the world. At the same time, Google accepted 3D models only with the requirement that they were textured and equipped with the correct geographical reference. Compared to many other popular packages, SketchUp has a number of features that are positioned as advantages. The main feature of this program is the almost complete absence of pre-configuration windows. All geometric characteristics during or immediately after the end of the tool are set from the keyboard in the Value Control Box. Another key feature is the Push/Pull tool, which allows any plane to be "pulled out" to the side, creating new side walls as it moves. You can move the plane against the predetermined curve, using a special tool Follow Me. The program is also characterized by extreme accuracy of calculations and measurements.